Effects of Bacterial Culture and Calcium Source Addition on Lead and Copper Remediation Using Bioinspired Calcium Carbonate Precipitation - Xue, Zhong-Fei; Cheng, Wen-Chieh; Wang, Lin; Wen, Shaojie (Frontiers in Bioengineering and Biotechnology, 2022)
Lead and copper ions from wastewater induced by metallurgical processes cause accumulation in soils, threatening plants and human health. The bioinspired calcium carbonate precipitation is proven effective in improving the cementation between soil particles. However, studies on capsulising heavy metal ions using the bioinspired calcium carbonate precipitation are remarkably limited. The present study conducted a series of test tube experiments to investigate the effects of bacterial culture and calcium source addition on the remediation efficiency against lead and copper ions. The calcium carbonate precipitation was reproduced using the Visual MINTEQ software package to reveal the mechanism affecting the remediation efficiency. The degradation in the remediation efficiency against lead ions relies mainly upon the degree of urea hydrolysis. However, higher degrees of urea hydrolysis cause the remediation efficiency against copper ions to reduce to zero. Such high degree of urea hydrolysis turns pH surrounding conditions into highly alkaline environments. Therefore, pursuing higher degrees of urea hydrolysis might not be the most crucial while remedying copper ions. The findings shed light on the importance of modifying pH surrounding conditions in capsulising copper ions using the bioinspired calcium carbonate precipitation.